2020
DOI: 10.1016/j.pbi.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted evolutionary trajectories of plant transcription factors

Abstract: Because of their prominent roles in plant development, transcription factors (TF) play central roles as drivers of innovation in the evolution of the green lineage (viridiplantae). The advent of massive sequencing combined with comparative genetics/genomics allows a rigorous investigation of how TF families have contributed to plant diversification from charophyte algae to bryophytes to angiosperms. Here, we review recent progress on TF family reconstruction and the identification of distantly related TFs pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…When considering chlorophyll degradation, it is also important to consider the various cellular and tissue-specific gene expression patterns that relates to changing contexts in which chlorophyll is degraded in the green lineages. Indeed, the extent of coevolution of senescence and the hormonal cues that regulate the PAO/phyllobilin pathway remain to be determined (Thomas et al, 2009;Bowles et al, 2020;Lai et al, 2020). In Arabidopsis, all eight genes involved in the core PAO/phyllobilins pathway are under a complex transcriptional control that involve multiple families of transcription factors that are in turn under hormonal control (Kuai et al, 2017;Aubry et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering chlorophyll degradation, it is also important to consider the various cellular and tissue-specific gene expression patterns that relates to changing contexts in which chlorophyll is degraded in the green lineages. Indeed, the extent of coevolution of senescence and the hormonal cues that regulate the PAO/phyllobilin pathway remain to be determined (Thomas et al, 2009;Bowles et al, 2020;Lai et al, 2020). In Arabidopsis, all eight genes involved in the core PAO/phyllobilins pathway are under a complex transcriptional control that involve multiple families of transcription factors that are in turn under hormonal control (Kuai et al, 2017;Aubry et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Again here, focusing on model species with high quality genomes will be necessary to identify potential cis elements and transcription factors involved. It remains unclear how this pathway could be maintained under similar regulation (or at least in response to similar environmental cues, in a similar way) during the complex evolution/expansion/alteration of various transcription factor families in the green clade (Lai et al, 2020). More work is needed to identify the extent of conservation of the gene regulatory networks and their connexion to various environmental/hormonal cues (Fürst-Jansen et al, 2020) that regulate the PAO/phyllobilin pathway, and that degrades chlorophyll in a safe and efficient manner.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed whether the identified genes were at the same genomic location or not by measuring the overlap of the three predicted gene sets. We conducted a similar analysis on nine transcription factor (TF) subfamilies, for which we assumed that the annotation process would be easier since they had a more conserved structure and, although having undergone expansion events, were not evolving under a birth-and-death model (Lai et al, 2020). The TF dataset contained between 874 and 1,041 genes, according to the annotations, and this number was similar to that of LRR-CR.…”
Section: Resultsmentioning
confidence: 99%
“…Some duplicates might be targets of the novel miRNA genes identified in this study. In the present study, many new genes, including TF genes, were identified, which may be responsible for the changes affecting the biochemical properties of the TF protein or its expression pattern (Lai et al, 2020). Besides, a few coherent pairs composed of novel miRNAs and new genes were also identified.…”
Section: Discussionmentioning
confidence: 96%
“…TFs are regulators and they carry information, which constantly updates plant development programs based on the modifications in environmental conditions, currently available resources, and sites of active organogenesis (Lai et al, 2020; Lanctot and Nemhauser, 2020. They participate in various processes, including development, immune and stress responses, and light and hormonal signaling (Schmitz and Theres, 2005).…”
Section: Discussionmentioning
confidence: 99%